Selection of Operation and Maintenance Stategic Partner Using AHP-VIKOR Model - Maryono Maryono (IPTEK Journal of Proceedings Series, 2020)
In order to increase CFSPP (Coal Fired Steam Power Plant) ABC actual EAF (Effective Availability Factor) from 76% in 2019 to designed EAF 85% by taking into consideration of investment funding hardship, PT.ABC initiate to select O&M (Operation and Maintenance) Strategic Partner, but it is not an easy decision and is associated with complexity. The purpose of this paper is to propose multi criteria decision making (MCDM) approach to effectively select the best partner out of 5 pre-selected partner candidates. The approach using AHP to calculate criteria weights, then VIKOR to get the final ranking result. The criteria and sub criteria define from experts’ discussion and literature review. Weights of 3 main criteria namely partner, collaboration and performance-oriented criteria are 0.113, 0.446 and 0.441. Alternative A1 is the first rank. There are 11 sub-criteria, with 3 biggest weights: 0.225 for project expectation, 0.162 for trust and 0.119 for technological capability. Project expectation and technological capability are from performance-oriented criteria while trust is part of collaboration-oriented criteria. This study can be useful for researchers to better understand of partner selection process and MCDM approach in theoritically, as well to companies in designing better partner selection system.